Konsep Nilai Pemberitaan Geopark Merangin pada Media Massa Online - Setiawan, Deddy; Mihardja, Eli Jamilah (UNIVERSITAS SARI MUTIARA INDONESIA, 2024)
Merangin Geopark is an area that has unique geology, biodiversity, and significant cultural and social values. This research involves analyzing the narratives used in the news coverage of Merangin Geopark to understand how the concept of geopark value in the stories conveyed to the public through the media. This research aims to analyze the concept of geopark value in news narratives with a case study on Merangin Geopark. This research method uses a qualitative approach by collecting and analyzing various news sources about Merangin Geopark. The data collected is then analyzed to identify the concept of geopark value depicted in the news narrative. The results showed that the news narrative of Merangin Geopark reflects the concept of geopark values which include aspects of natural beauty, geological uniqueness, environmental sustainability, cultural heritage and Geopark development. The concept of these values is reflected in the stories conveyed to the public, both through the depiction of amazing geological characteristics, abundant biodiversity, and local wisdom related to the culture and traditions of the local community, In addition, the values presented in the news narrative, such as uniqueness, vulnerability, and sustainability, are closely related to the characteristics of Merangin Geopark. It can be said that the prominence of news narratives in communicating the importance of geopark preservation and development depends not only on the content of the narrative itself, but also on factors such as news dissemination, the intended audience, and the social context.